Hemoglobin and hematocrit in mountain bike sports under extremly strenuous more days lasting endurance impact - Wirnitzer, K. (International Congress Mountain & Sport. Updating study and research from laboratory to field. 11th-12th November 2005. Rovereto (TN) - Italy. Programme and book of abstracts, 2005)
Changes in hematological parameters haemoglobin (Hb), hematocrit (Hct) and plasma volume (PV) are known to considerably influence physical performance, especially in endurance sports. Performance in endurance sports such as road cycling and mountain biking (MTB) mainly depends on aerobic capacity. An increase in total hemoglobin mass and PV shows enhanced aerobic performance. The increase in PV is usually more pronounced than the increase in red cell volume, which results in lower Hb and Hct values in endurance athletes. As a consequence of PV expansion aerobic performance capacity is enhanced due to reduced blood viscosity, thereby optimized microcirculation and improved oxygen delivery capacity to the working muscle. Some articles have been released dealing with adaptations of ematological variables during ultra endurance and stage cycling events. However, there is no single publication on changes in hematological system referring to MTB sports. Therefore, the aim of this paper is to determine changes in Hb, Hct and PV during the hardest MTB marathon race in the world. Within eight consecutive stages the TAC 2004 covers a total altitude of 22.500 m and milage of 662 km (daily average: 2.812,5 m and 82,75 km). Referring to the current literature available the author hypothesised: 1) Acute increase of both Hb and Hct levels as a consequence of PV decline caused by prolonged strenuous endurance exercise, thermal stress and hydration status and 2) Decrease in both Hb and Hct levels as a result of PV expansion due to this severe multiple day MTB marathon. Method: Hb and Hct levels are reported of mountain bikers who successful finished the TAC 2004 with complete hematological data sets recorded (n = 6). Subjects, five men and one woman, credibly not taking any kind of doping, are well endurance trained amateur athletes and all experienced in participating MTB marathon races. Within four measurements 48 venous blood samples were drawn to estimate development of Hb and Hct levels by taking capillary blood from finger tip. To determine baseline levels of Hb and Hct, blood samples are taken before the start of the MTB stage race (E0) after some minutes of rest in supine position. After each individual finished first stage E1, fourth stage E4 and sixth stage E6, post exercise Hb and Hct concentrations were measured. Relative changes in PV (Ä%PV) were calculated from Hb and Hct values according to the equation of Strauss 1951. Values of p<0,5 are determined to be significant. Results: Referring to only one single female athlete and the fact that results do not show any significant difference compared to male athletes, I decided to evaluate hematological variables albeit of gender. Results are shown in Table 1. 1) During the first stage of the TAC 2004 a relative increase in Hb and Hct occurred as a consequence of PV decline: The relative increase in Hb is 17,81 (p=0,003), the relative increase in Hct is 1,97 (p=0,2) and the relative increase in PV is -12,68 (p=0,04). 2) In the course of the MTB stage race post exercise of both the relative increase in Hb and Hct decreased as the result of PV expansion from E1 to E4: -19,77 (p=0,004), -14,67 (p=0,4) and +7,29 (p=0,07), respectively, and from E1 to E6: -23,26 (p=0,004), - 17,38 (p=0,3) and +7,82 (p=0,06), respectively. Conclusion: It can be concluded that during E1 of the TAC 2004 an increase in Hb and Hct levels occurred as a consequence of PV decline, showing the acute effect of strenuous endurance impact on hematological variables. Although the number of MTB athletes finishing this severe marathon stage race was small, the measurements show that under extreme conditions Hb and Hct tend to drop due to PV expansion. Hemodilution in terms of extended PV is well documented as a long term effect of repeated endurance strains. The results of this study prove my hypothesis and confirm the findings of recent papers. Referring to the sparse knowledge of changes in hematological parameters in MTB endurance sports there is more research needed.